Superconductors - Narlikar, A. V., 1940- (Oxford University Press, 2014)
'Superconductors' is neither about basic aspects of superconductivity nor about its applications, but concentrates mainly on superconducting materials. It is not an encyclopaedia, describing each and every superconductor that exists. Instead, it is about those materials that have represented important milestones in this exciting field, because of their fundamental scientific interest, their technological applications, or the challenges they present (e.g. the magnetic superconductors).